Auditoría financiera y su incidencia en la razonabilidad de los estados financieros de la empresa ferretera Promacero del cantón Pelileo, perìodo 2019. - Tirado, Luis Mario (2022)
ABSTRACT The following research project called "Financial audit and its impact on the reasonableness of the financial statements of the hardware company Promacero at Pelileo canton, period 2019." Its objective was to carry out a financial audit to know the impact on the reasonableness of the financial statements of the hardware company Promacero of the Pelileo canton for the 2019 period. An audit is a critical and necessary examination of the financial statements' information in order to ensure compliance with the accounting cycle and to provide a professional judgment on the financial statements' fairness. The research work is divided into chapters: in the first chapter the referential framework, the problem posed, justification, general and specific objectives of the research are defined, the second chapter is made up of the state of the art, investigative background and conceptualization of variables , in the third chapter the methodology, type, design, approach, and level of the investigation are detailed, in addition to the sample and study population, and data collection techniques and instruments, in the fourth chapter the audit phases are promoted such as Planning, Execution and Communication of Results, and finally in chapter five the main conclusions and recommendations determined in the audit findings are established, such as the lack of procedure manuals for the components under study. Keywords: Internal control, Audit, Financial Information, Reasonableness. Firmado electrónicamente por: MISHELL GABRIELA SALAO ESPINOZA